Vamana purana / Bibek Debroy, Dipavali Debroy ; penerjemah, I.G.A.Dewi Paramita ; editor, J.Wayan Maswinara - DEBROY, Bibek ; Debroy, Dipavali ; Paramita, I.G.A. Dewi ; Maswinara, I.Wayan (Paramita, 2002)
viii, 120 hlm ; 19 cm